Identification and Management of Intermediate Risk Patients in the Chest Pain Unit. Issue 1 (March 2020) - Prasad, Pooja; Sharma, Ajay Nair; Vipparla, Navya Sree; Majid, Muhammad; Daniela, Aro; Howell, Stacey J.; Wilson, Machelle D.; Amsterdam, Ezra A.
Abstract : Objective: We examined low risk (LR) patients admitted to our chest pain unit (CPU) with negative cardiac injury markers, normal electrocardiogram, and clinical stability. We hypothesized that there is a sub-group of intermediate risk (IR) patients within the larger LR population. Methods: Criteria for IR were the aforementioned 3 indicators of LR and ≥1 of the following: (1) known coronary artery disease (CAD), (2) men ≥45 yo, women ≥55 yo, and (3) ≥3 cardiac risk factors. We compared patient characteristics, use of pre-discharge testing (PDT), and major adverse cardiac events (MACE). Results: IR patients numbered 371, whereas LR patients totaled 70. IR patients were older (61 vs 46 years), more had known CAD (28 vs. 0%), had a higher median number of risk factors (2 vs. 1) and were less likely to be women (49 vs. 81%), all P < 0.0001. IR patients received a greater median number of tests compared with LR patients (1 vs. 0, P < 0.0001). Conclusions: Among the IR group, 16 patients (4%) had a cardiac event at the index CPU visit, 2 (0.5%) experienced MACE at 30-day follow-up, and 2 (0.5%) had MACE at 6 months follow-up. No LR patients had MACE at any point in the study. Thus, the majority of CPU patients are IR, have more risk factors than LR group, and are more likely to receive PDT. IR patients were managed safely in a CPU, while maintaining low rates of MACE post-discharge.